Physiology of cerebrospinal fluid circulation. Issue 5 (October 2019) - Shapey, Jonathan; Toma, A.; Saeed, S.R.
Abstract : Purpose of review: This article describes the physiology of cerebrospinal fluid (CSF). We review current evidence and new concepts relating to CSF physiology with respect to CSF secretion, circulation and resorption and we highlight key pathophysiological associations including the relationship between CSF and intracranial pressure. Recent findings: CSF secretion occurs primarily via the choroid plexus. Various transport mechanisms facilitate CSF secretion but the role Aquaporins play in this process is a recent discovery and an area of ongoing research. CSF circulation is a dynamic process but the importance of the perivascular 'Glymphatic system' and extraarachnoidal pathways of resorption are relatively new concepts. Summary: CSF physiology is dependent on various interacting factors and is critical for normal brain development and function.